2018
DOI: 10.3389/fphar.2018.01266
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Modulates High Glucose-Incubated Human Umbilical Vein Endothelial Cells Proliferation and Apoptosis Through AMPK/CREB/BDNF Pathway

Abstract: Cardiovascular disease (CVD) is a leading cause of mortality and morbidity among patients with diabetes. Endothelial dysfunction is an early physiological event in CVD. Metformin, a common oral antihyperglycemic agent, has been demonstrated to directly affect endothelial cell function. Brain-derived neurotrophic factor (BDNF), originally discovered in the brain as a neurotrophin, has also been reported to play a protective role in the cardiovascular system. In our study, we demonstrated that high glucose (HG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…Although it is well known that HG plays a key role in diabetic endothelial dysfunction and atherosclerosis, the mechanisms responsible for HG-induced endothelial damage remain to be elucidated. The HG (33 mM)-induced HUVECs injury model was employed to investigate the underlying mechanisms of endothelial injury, and further investigated cytoprotection of H 2 S. In the present study, HG treatment for 24 hrs caused a significant reduction in the cell viability of HUVECs, which was consistent with the results from Han et al, 34 However, several studies demonstrated that the inhibitory effects of HG on HUVEC viability were observed after 48-hr 35 and 72-hr treatment. [36][37][38][39] The inconsistency regarding the HG treatment duration across different studies may be due to the different culture conditions, different sources for obtaining HUVECs, or different experimental protocols, which may require further examination.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is well known that HG plays a key role in diabetic endothelial dysfunction and atherosclerosis, the mechanisms responsible for HG-induced endothelial damage remain to be elucidated. The HG (33 mM)-induced HUVECs injury model was employed to investigate the underlying mechanisms of endothelial injury, and further investigated cytoprotection of H 2 S. In the present study, HG treatment for 24 hrs caused a significant reduction in the cell viability of HUVECs, which was consistent with the results from Han et al, 34 However, several studies demonstrated that the inhibitory effects of HG on HUVEC viability were observed after 48-hr 35 and 72-hr treatment. [36][37][38][39] The inconsistency regarding the HG treatment duration across different studies may be due to the different culture conditions, different sources for obtaining HUVECs, or different experimental protocols, which may require further examination.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the inhibition of the inflammatory response and vascular calcification in VSMC by metformin [24,25]. Metformin also inhibits proliferation of tumor and endothelial cells [26,27]. In our study, metformin decreased VSMC proliferation in the high-glucose condition.…”
Section: Discussionsupporting
confidence: 52%
“…MET exerted protective effect against hyperglycemia-induced endothelial impairment, which was contributed to MET improving HG-inhibited GLI1 activity and BNIP3 expression in HUVECs ( Niu et al., 2019 ). MET was also reported to promote angiogenic potential of HUVECs probably by the regulation of endocan dynamics under high glucose condition ( Zolali et al., 2019 ) and modulate high glucose-induced HUVECs proliferation and apoptosis through AMPK/CREB/BDNF Pathway ( Han et al., 2018 ). However, our study focused on exploring the mechanism of MET in modulating hyperglycemic-induced oxidative stress in order to open a new perspective of MET in the treatment of GDM (HG).…”
Section: Discussionmentioning
confidence: 99%